Stents in Renal Artery Bifurcation Stenosis: A Case Report. (12th July 2011) - Leonardou, Polytimi; Pappas, Paris
Abstract : A 39-year-old patient presented with poorly controlled hypertension, and she was referred to renal angiogram and potential renal angioplasty. Renal angiogram showed a bifurcation lesion of the right renal artery. A guide wire was used to cross the upper branch, while the lower branch was protected by another same-type guide wire through the same introducer. Two thin monorail balloons were used to dilate the two branches; however, despite balloon dilatation, the stenosis of the vessels persisted. The "kissing balloon" technique was then attempted by simultaneously inflating both branches using the same balloons, but more than a 70% residual stenosis persisted in each branch. Two stents were finally placed in a "kissing" way through the main renal artery. The imaging and clinical results were good, without any procedure-related complications. Three years clinical followup was also good, without any reason for further interventional approach.